Analisis Debit Banjir Sungai Ciujung Tol Merak Km 57 Kabupaten Serang - Siti Astycha Ananda Sofyan; Andi Adillah Firstania (Syntax Corporation Indonesia, 2024)
Ciujung River is located in Serang Regency, Banten, where the river is on the right and left sides of the Merak Toll Road connecting Jakarta-Serang. The length of the Ciujung River on the right side is 6.27 Km and the left side is 6.83 Km. Extreme rainfall that occurred in the last two years resulted in inundation of surrounding settlements and the Jakarta-Merak Toll Road at Km 57-59. The toll road was flooded with a depth of 1 meter caused by the overflow of the Ciujung River, which caused severe congestion during the rainy season and economic losses for local residents. The worst flood ever occurred in 2013 where almost 1 month there was a disaster on the Merak Km 57-59 toll road due to flood water puddles that were almost 1 m deep. This flood actually occurred long before 2013, it can even be said to be an annual flood for local residents who live on the banks of the river. But because water enters the Merak Toll Road which is a means of trade transportation that has high economic value, it has only been noticed the cause of this flood. This study aims to find the cause of flooding why it occurs only at the location of the 57-59 Km Toll Road and the completion of the flood using various variables such as river dimensions, rainfall, watershed area, etc. and analyzed using the HSS Snyder and ITB1 flood hydrograph methods.